Study on the Effect of Pulsed Current TIG Welding Parameters on Weld Profile of Al-SiC Composite Weldments Using L9 Orthogonal Array’s Experimental Design - Pichumani, Sivachidambaram; Srinivasan, Raghuraman; Ramamoorthi, Venkatraman (International Journal of Engineering and Technology, 2018)
Investigation of Al-SiC composite weldmentâ€™s, weld profile such as weld depth, weld width and (D/W) ratio, during various conditions of PCTIG welding designed using L9 orthogonal array. The experiment is designed using L9 orthogonal array to reduce the number experiments from 81 to 9 experimental conditions. The parameters considered for PCTIG welding are peak current, base current, pulse frequency and pulse on time. Regression equation, contour plot analysis are developed. This statistical & mathematical analysis are used to find the influence of each pulsed current parameter at each level by pulsed current parameters on weld depth, weld width and (D/W) ratio during PCTIG welding of Al-SiC composite. Optimization of the pulsed current TIG welding parameters is also carried out to and the optimized predicted value is compared with experimental value. PCTIG welding parameters such as peak current of 160A, base current of 60A, pulse on time as 50% and pulse frequencyas 5Hz shows highly desired results such as high weld depth = 2.5mm, minimum weld width = 6.5mm and higher (D/W) ratio = 0.38.Â